Development of Canva-Based Electronic Student Worksheet (E-LKPD) to Improve Student Biology Learning Outcomes - Musdalifah Musdalifah; Sonja Verra T. Lumowa; Vandalita M. M. Rambitan (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to make and develop electronic worksheet students (E-LKPD) that can be used by teachers in implementing learning in using IT-based learning media. This type of research is research and research and development (R&D) with a 4D development model (Define, Design, Development, and Dissemination). The sample in this study was biology teachers and students of SMA Negeri 1 Kaliorang. The results of the validation of media, material, and language experts respectively are 84.41% (very feasible), 82.35% (very feasible), and 69.41% (feasible). The results of the Biology Teacher Repson related to product practicality obtained a percentage of 92.50% (very practical), while the results of the trial to see the response of students obtained a percentage of 82.50% (very practical). The results of the effectiveness test using the paired sample t-test test showed that there was an effect of the use of canva-based e-LKPD in improving the learning outcomes of high school students in East Kutai on biotechnology material